2015
DOI: 10.1002/hed.24268
|View full text |Cite
|
Sign up to set email alerts
|

Disease‐free survival after salvage therapy for recurrent oropharyngeal squamous cell carcinoma

Abstract: For recurrent oropharyngeal SCC, HPV-positive tumor status, surgical salvage, and clinical response to salvage therapy are independently associated with improved OS, but not DFS after salvage. Surgical margin is the only independent predictor of DFS. © 2015 Wiley Periodicals, Inc. Head Neck 38: E1501-E1509, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 29 publications
(84 reference statements)
2
23
0
1
Order By: Relevance
“…In a study by Maquieira et al, p16 expression was also prognostic for OS but not for regional recurrence‐free survival. Another study by Joseph et al examined recurrent oropharyngeal SCCs and reported that HPV positivity was prognostic for favorable OS, but not for disease‐free survival after salvage therapy. In our study, of all the clinicopathological parameters, only older patient age was associated with regional recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Maquieira et al, p16 expression was also prognostic for OS but not for regional recurrence‐free survival. Another study by Joseph et al examined recurrent oropharyngeal SCCs and reported that HPV positivity was prognostic for favorable OS, but not for disease‐free survival after salvage therapy. In our study, of all the clinicopathological parameters, only older patient age was associated with regional recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…These epidemiologic changes are driven by increasing oral exposure to human papillomavirus (HPV) infection . HPV‐positive OPSCC patients are more likely than HPV‐negative OPSCC patients to be white, to be younger, and to have better survival both at the time of the primary diagnosis and upon disease recurrence …”
Section: Introductionmentioning
confidence: 99%
“…2,3 HPV-positive OPSCC patients are more likely than HPV-negative OPSCC patients to be white, to be younger, and to have better survival [4][5][6] both at the time of the primary diagnosis and upon disease recurrence. [7][8][9][10][11] To date, in the majority of studies evaluating the prognosis for OPSCC, the patient populations have been composed primarily of male and white non-Hispanic patients; this is a reflection of the demographics of the disease. 12 Although the incidence of OPSCC is lower among women and nonwhites, we have recently shown that the majority of OPSCCs in these groups are HPV-related.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, there are limited data on HPV status and survivals in recurrent oropharyngeal tumors. In a recent study, Joseph et al found that HPV‐positive status improved overall survival, but not recurrence‐free survival.…”
Section: Discussionmentioning
confidence: 99%